Horrid henry's joke book ebook - Simon, Francesca (Horrid Henry., 2010)
Warning: Too rude for parents and for slimy toad little brothers! These are Horrid Henry's very own jokes: the jokes that grossed out Mom and Dad... that made Aunt Ruby run home... that sent Miss Battle-Axe screaming from class. Be horrid! Read Henry's jokes. Then tell them to the world!